Análise crítica dos produtos de mobilidade sentada - cadeiras de rodas - utilizados por crianças e adolescentes com paralisia cerebral em Natal/RN e outros municípios do Rio Grande do Norte - Galvão, Cláudia Regina Cabral (2006)
The objective of this work is to critically analyze the seated mobility adaptive equipment, wheelchair, used by non-ambulatory children/adolescents diagnosed with cerebral palsy of the quadriplegy type with ages in between 0-18 years old in the municipal city of Natal/RN and of other ones in the state of Rio Grande do Norte. This study is characterized as descriptive as it took into consideration the individualized conditions of each child/adolescent and of their home environment, and also evaluates the condition of the used seated mobility devices such as wheelchairs or strollers. Thirty three (33) subjects which had a wheelchair prescribed by a healthcare professional specialist in adaptive equipment within the past 3 years were selected. A questionnaire was applied through a phone with the patient s primary care giver or parents. The results obtained showed that all the equipment being used had an anatomical seat and back and the tilt system mechanism and even though most of the patients required small individual adjustments upon receiving the wheelchair in order to accommodate to the patients characteristics. From the point of view of the caregiver/parents interviewed, 97% described satisfied with the equipment and report assistance with mobility (97%), comfort (82%) and good posture (82%) as the main positive aspects from the equipment. The results also describe the aspects related to the maintenance, time used and activities developed that were reported by the patients. The conclusion therefore is that in order to select the equipment to meet the needs of the consumer it is necessary that: an appropriate wheelchair prescription takes place, the up-to-date knowledge of equipment available in the market, the appropriate use of the resources from the concession programs of the government that purchase equipment and the establishment of link in between the manufacturers, patients and the caregivers